A novel recyclable hydrolyzed nanomagnetic copolymer catalyst for green, and one-pot synthesis of tetrahydrobenzo[b]pyrans - Behrooz Maleki; Samaneh Sedigh Ashrafi; Pouya Ghamari Kargar; Azita Alipour; Zohreh Pahnavar; Pegah Ebrahimzadeh (Scientific Reports)
Abstract Polymer-based catalysts have garnered significant interest for their efficiency, reusability, and compatibility with various synthesis processes. In catalytic applications, polymers offer the advantage of structural versatility, enabling functional groups to be tailored for specific catalytic activities. In this study, we developed a novel magnetic copolymer of methyl methacrylate and maleic anhydride (PMMAn), synthesized via in situ chemical polymerization of methyl methacrylate onto maleic anhydride, using benzoyl peroxide as a free-radical initiator. This polymerization process results in a robust copolymer matrix, which was subsequently hydrolyzed in an alkaline aqueous solution to introduce additional functional groups, yielding hydrolyzed PMMAn. These functional groups enhance the copolymer’s ability to support the deposition of magnetic nanoparticles and participate in catalytic reactions. Following hydrolysis, we fabricated a unique magnetic composite, Fe3O4@Hydrol-PMMAn, by in situ coprecipitating Fe3O4 nanoparticles onto the hydrolyzed copolymer, creating a stable nanocatalyst. The structural and magnetic properties of Fe3O4@Hydrol-PMMAn were thoroughly analyzed using FTIR, XRD, SEM, EDX, VSM, and TGA. The Fe3O4@Hydrol-PMMAn nanocatalyst demonstrated remarkable catalytic performance in synthesizing tetrahydrobenzo[b]pyran derivatives through a three-component reaction, conducted without solvents to support green chemistry principles. A series of reaction parameters were optimized, including solvent choice, catalyst loading, and recyclability. The catalyst performed efficiently across a broad range of aldehydes, delivering high product yields (81–96%) with rapid reaction times (5–30 min) at a low catalyst loading of 0.015 g. A hot filtration test confirmed the heterogeneous nature of the nanocatalyst, which could be recycled up to four cycles with minimal loss in activity. The high yield, short reaction time, solvent-free conditions, and excellent reusability make Fe3O4@Hydrol-PMMAn a promising catalyst. These findings underscore its potential for converting waste products into valuable compounds, highlighting its utility in organic transformations and sustainable synthesis practices. Collectively, this work demonstrates that Fe3O4@Hydrol-PMMAn is highly effective for organic compound synthesis, advancing the development of versatile, sustainable nanocatalysts.